Elaboración de un modelo de gestión administrativa para la unidad educativa intercultural bilingüe “Ciudad de Macas” de la parroquia Sevilla Don Bosco, cantón Morona, provincia de Morona Santiago para El año 2016 - Antria Florentina, Atamaint Entsakua (2017)
The main objective of this research is to propose an Administrative Management Model for its application to the Intercultural Educational Unit Bilingual city of Macas de la Parroquia Sevilla Don Bosco, Morona canton, province of Morona Santiago, for the year 2016. The present study was born with the need to establish management tools that allow the entity under study to strengthen the administrative system, as evidenced within the company delays in the execution of administrative processes and consequently no improvement of services . With the application of the proposal, the aim is to optimize the administrative processes, so that the staff perform efficiently and efficiently in their area of work, to the benefit of those involved and mainly to increase the quality of the service to the users of the city of Macas. For the above, for the development of the present investigation different methods were used, such as inductive, deductive, historical, statistical, and analytical; In addition, techniques such as direct observation, interview and survey were used to obtain real information about the current situation of the company under study. For the above, among the main results obtained in this work, it can be noted that the company does not have documented objectives and values, there is no structural organization chart or manual of functions, the selection of personnel is done empirically , staff are not permanently trained. In addition, it can be seen that 63% of the employees have been working for 1 to 2 years, 88% of the staff of the Unit correspond to Teachers, 81% of the staff if they know the mission and institutional vision, 100% do not know , objectives, strategies, values and policies of the organization, 69% have received training per year, 100% mention not knowing a manual of functions of the establishment, 69% qualify the organization's work environment as excellent, 81 % states that it is not taken into account in decision-making and 100% of staff declare that their work performance has not been measured. With the aforementioned results, the administrative management model was established according to the 4 fundamental pillars of the same, such as: planning, organization, direction and control. With regard to Planning, the mission and vision were reformulated, objectives, strategy and policies were formulated, as well as a training plan. In the Organization, the organicfunctional structure was considered and the main processes of the entity were determined. The Directorate establishes a guide based on decisionmaking, integration, motivation and supervision and finally in the control, an instrument is proposed to measure the performance of the Human Talent of the Educational Unit. Finally, they establish the conclusions and recommendations, which are defined based on the need to propose a model of administrative management in the City of Macas Educational Unit, which is based fundamentally on planning (restructuring of mission and vision, setting goals , policy strategies and training plan). Organization (organic-functional structure and structure of processes). Management (management guide based on decision making, integration, motivation, communication and supervision). Control (Human Talent Performance Measurement Instrument).